1980
DOI: 10.1177/004051758005001104
|View full text |Cite
|
Sign up to set email alerts
|

A Rapid Method for Determining the Sorption Characteristics of Textile Materials 1

Abstract: A new method is presented for the rapid determination of the water-sorption properties of wool over the complete range of relative humidities. The apparatus and method of operation are described, and an example of a sorption curve for merino wool top is given.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…The kinetic parameters were obtained by applying Fick's diffusion equation to a cylinder. Although early studies had claimed that wool attained very rapid equilibrium in sorption experiments, subsequent experiments clearly showed that it took an appreciable time for wool to achieve equilibrium in an air flow using 1g samples (Finnimore & Wortmann, 1980).…”
Section: Introductionmentioning
confidence: 98%
“…The kinetic parameters were obtained by applying Fick's diffusion equation to a cylinder. Although early studies had claimed that wool attained very rapid equilibrium in sorption experiments, subsequent experiments clearly showed that it took an appreciable time for wool to achieve equilibrium in an air flow using 1g samples (Finnimore & Wortmann, 1980).…”
Section: Introductionmentioning
confidence: 98%
“…Water retention reaches 40-45%, because of low crystallinity, the existence of interfibrillar micro-capillaries and numerous hydrophilic groups. 28,[30][31][32] Leeder and Watt 33 have found that in 25% RH there are about 1.4 water molecules per one amine group, while in 65% RH there are 2.6 water molecules. An amine group is able to produce three hydrogen bonds, and if it is accessible, it may bind to three water molecules (in about 80% RH).…”
Section: Sorption and Changes In Concentration Of Nicotine And 3-epmentioning
confidence: 99%